Perancangan Sistem Aplikasi Penyewaan Mobil Berbasis Mobile - Juniartha, I Wayan Agus; Astawa, I Gede Santi (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2024)
Nowadays, people tend to search for goods or services through their mobile device using an electronic marketplace. In Bali, a rental business for tourist, weekend events, and other events grow rapidly. This business provides services that rents various kinds of car such as innova, alphard, alya, and others that are commonly used in weekend events. However, unfortunate for rental service entrepreneurs who have high prospects, many of them are using the traditional method of marketing and sales such as word-of- mouth. Moreover, many of them not catching up with the current development of the rental car. By listing the services on the rental, easier for the customer to find the car they want that fit their needs and budget. Also, by utilizing rental car will save the customer time, because the customer can just search, compare, and book to rent car without leaving home. The purpose of this research project is to create a mobile- based application of market place that accommodates entrepreneurs renting car. Our purposed mobile-based rental uses the prototyping method to build this mobile-based application